Detection of tetracycline and ampicillin resistant E. coli and Salmonella species from hospital wastewater (Bangladesh Veterinarian, 2024)
Escherichia coli (E. coli) and Salmonella spp. were found in hospital wastewater. The highest (E = (6.2 ± 1.8) x 109; S = (4.3 ± 2.2) x 109) and lowest (E = (1.4 ± 1.2) x 109; S = (1.1 ± 1.8) x 109) Total Viable Count (TVC) were in Shaheed Suhrawardy Medical College Hospital (SSMCH) and National Institute of Ophthalmology Hospital (NIOH), respectively. The overall occurrence of E. coli and Salmonella spp. was 80% and 87%, respectively, with 100% occurrence in SSMCH and National Institute of Cardiovascular Diseases Hospital (NICVDH) for Salmonella spp. (p ≤ 0.036). Prevalence of E. coli was low (72%) in winter (November - February). Both types of bacteria were resistant to Tetracycline whereas and 97.5% of E coli were resistant to ampicillin. Gentamycin was more effective than other antibiotics. Rational use of antibiotics is suggested, and hospital management practice should be followed as defined by the Joint Commission International for Hospital Accreditation.Bang. vet. 2023. Vol. 40, No. 1 – 2, 16 – 24